The hospital at the end of the world : a novel - Key, Justin C. (Harper, 2026)
"From New York Times bestselling author Justin C. Key, a thrilling novel set in the near future where artificial intelligence runs the world, following a young doctor as he unravels family secrets In a year not so far from our own, society is run by the shepherds, a global AI system. The shepherds have controlled every aspect of Pok's twenty years of life-they decided what schools Pok went to, what jobs he was eligible for, what foods he ate, and even his medical care. He's content living a carefree life until his father is killed by a mysterious illness. Searching for answers, Pok decides to follow in his father's footsteps and travel to the very last hold-out city and train at the one hospital that still practices human-led medicine: Hippocrates. As Pok works his way through medical school, he's pulled into the terrifying mystery of a strange illness plaguing immigrants who grew up under shepherd rule. Will Pok be able to uncover what's truly going on in the inner sanctum of the shepherds? The Hospital at the End of the World is a medical thriller for the ages exploring the intersection of technology, health, and what it means to be truly free"-- Provided by publisher.